2022
DOI: 10.1371/journal.pone.0275331
|View full text |Cite
|
Sign up to set email alerts
|

Risk perception, community myth, and practices towards COVID-19 pandemic in Southeast Ethiopia: Community based crossectional study

Abstract: Objective The objective of this study was to assess risk perception, community myths, and preventive practice towards COVID-19 among community in Southeast Ethiopia, 2020. Methods Community-based cross-sectional study was conducted among 854 participants selected using a multistage sampling technique. Data were collected using a structured questionnaire adapted from previous literature. Descriptive statistics were done to summarize the variables. A generalized linear model with binary logistic specification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…Healthcare workers who lived a distance further away from their workplaces were more resilient than those who lived nearer. This is consistent with a previous study in Ethiopia, which showed that high levels of stress and perceived risk of contracting diseases for HCWs during epidemics were linked to living near their workplace health facilities [39]. The ndings of this study are also in line with a study done in Peru which indicated that HCWs' anxiety and mental distress decreased as the distance from the COVID-19 outbreak epicentre increased [40].…”
Section: Discussionsupporting
confidence: 92%
“…Healthcare workers who lived a distance further away from their workplaces were more resilient than those who lived nearer. This is consistent with a previous study in Ethiopia, which showed that high levels of stress and perceived risk of contracting diseases for HCWs during epidemics were linked to living near their workplace health facilities [39]. The ndings of this study are also in line with a study done in Peru which indicated that HCWs' anxiety and mental distress decreased as the distance from the COVID-19 outbreak epicentre increased [40].…”
Section: Discussionsupporting
confidence: 92%
“…Conversely, single or separated individuals may experience a greater burden of individual decision-making and caregiving, which could potentially contribute to an increase in their RP. However, it is important to note that the literature on this association is still inconclusive, since two other studies, conducted in Iran [ 56 ] and Ethiopia [ 57 ], did not find this association. This difference may be attributed to the fact that these studies were carried out in distinct countries, each with its unique cultural context.…”
Section: Discussionmentioning
confidence: 99%